2003
DOI: 10.1177/07419325030240030601
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Impact of Anchored Instruction on Teaching and Learning Activities in Two Ninth-Grade Language Arts Classes

Abstract: This study employed classroom observations and teacher and student interviews to examine the impact of anchored instruction on student and teacher behaviors in two inclusive ninth-grade language arts classes. Specifically, the investigators examined the effect of anchored instruction on (a) the length (long or short) and level (factual or interpretive) of questions asked by, and responses to student questions by, the classroom teacher; (b) the length and level of questions asked by, and responses made by, nint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 5 publications
1
30
0
Order By: Relevance
“…For other students, this could mean that they would have access to an audio version of the assigned text (Boyle et al 2003). A film could be used to anchor key concepts, providing students with dynamic visual images of key events, period clothing, architecture, and music, helping students to conceptualize relationships and emotions that are outside their range of experience (Rieth et al 2003).…”
Section: Differentiate Instructionmentioning
confidence: 99%
See 1 more Smart Citation
“…For other students, this could mean that they would have access to an audio version of the assigned text (Boyle et al 2003). A film could be used to anchor key concepts, providing students with dynamic visual images of key events, period clothing, architecture, and music, helping students to conceptualize relationships and emotions that are outside their range of experience (Rieth et al 2003).…”
Section: Differentiate Instructionmentioning
confidence: 99%
“…In text-based collaborative reading activities, such as literature circles (Dieker and Little 2005), anchored instruction (Rieth et al 2003), and problem-based learning (Bucalos and Lingo 2005), groups should be balanced by including a variety of student abilities and dispositions so that each student makes a unique contribution to the group process. Assigning student roles, such as "note-taker," "predictor," "questioner," "clarifier," "responder," and "summarizer," keeps students on task and helps them know what to do.…”
Section: Group Students Effectivelymentioning
confidence: 99%
“…Other researchers have developed instructional units around anchor videos, including To Kill a Mockingbird (Rieth, Bryant, Kinzer, Colburn, Hur, Hartman, & Choi, 2003) and Eyes on the Prize (Gersten, Baker, Smith-Johnson, Dimino, & Peterson, 2006). Both of these interventions included detailed analysis of the video to develop students' conceptual understanding, discussion, collaborative group investigation, and integration of information across social studies disciplines.…”
Section: Investigative Learningmentioning
confidence: 99%
“…Studies have shown the utility of ''anchored instruction'' for students with learning disabilities in language arts and mathematics (Bottge, Heinrichs, Chan, & Serlin, 2001;Reith et al, 2003) and ''functional application'' of academic content knowledge for students with severe disabilities to support their generalization of these skills to typical performance settings (Browder, Spooner, et al, 2006;Browder et al, 2009). For example, in addition to the instruction that Jamal would receive on interpreting units of a scale displayed on a graph during his geometry class, he could apply these skills by weighing himself in the men's locker room or at home and recording it on a graph.…”
Section: Incorporate Authentic Tasks Into Instructionmentioning
confidence: 99%